INFRASTRUCTURE SUPPLY OF THE ORGANIC SECTOR OF AGRICULTURAL PRODUCTION ON COOPERATION BASES - Kryuchko, L. S. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
The article considers the expediency of organic agricultural production with the definition of a number of advantages, such as economic, environmental and social. The conditions for the development of organic agricultural production are given, namely: the presence of large areas of environmentally friendly agricultural land; high fertility of soils; favorable climatic conditions; low level of use of mineral fertilizers, plant protection products; presence of potential consumers market; Export attractiveness of organic products for EU countries; provision of the agrarian sector of the economy by labor resources. The efficiency of production of organic agro production, which is determined by internal (organizational, techno-technological, economic, marketing) and external (economic, institutional, legal, natural-ecological, social) factors, is investigated. The reasons that hinder the efficiency of production of organic products in Ukraine, which can be attributed to: imperfect institutional support and lack of state financial support; Innovative passivity of most manufacturers and management structures; lack of awareness of producers regarding the specifics of organic production and the public regarding the benefits of organic products; the predominance of exports of organic raw materials; processing, production, wholesale and retail trade in organic products of consumption are still underdeveloped; deficit of grain and other agricultural crops of organic origin; insufficient number of cattle as the main producer of organic fertilizers; high cost of borrowed funds; high ethnogeny load on the area of ​​Central and Eastern Ukraine. The evolution of the organic agricultural market will lead to the development of the relevant infrastructure. Agriculture of Ukraine has all the conditions for the development of organic agricultural production, since the soil-climatic allow to significantly expand the volume of organic farming. Co-operation of the organic agricultural sector in Ukraine is presented in the form of dairy cooperatives, which are intended for the sale of milk at more attractive prices. The cooperative movement makes it possible to combine efforts to create real competition for powerful agrarian enterprises and, at the same time, to promote the spread of organic agricultural production.